Reduced ligand affinity leads to an impaired function of the adenosine A(2A) receptor of human granulocytes in sepsis - Kreth, Simone (Blackwell Publishing Ltd, 2009)
The enhanced release of reactive oxygen species by excessively activated polymorphonuclear leucocytes (PMN) is a key step in the pathogenesis of sepsis. Potent action of adenosine in inhibiting cytotoxic PMN functions has been documented. Recent data, however provide evidence that in sepsis a diminished capability of adenosine to inhibit the generation of oxygen radicals by PMN occurs. Here, we investigated the underlying mechanisms in an in vitro sepsis model and in PMN of sepsis patients. We report that lipopolysaccharide (LPS)-incubation of human PMN elicited the same increase in the half-maximal inhibitory concentration (IC(50)) of adenosine as observed in patients with septic shock. Coupling to adenylyl cyclase was impaired as well, as indicated by a decreased potency of adenosine to stimulate cyclic adenosine monophosphate (cAMP) accumulation. Ligand-binding studies conducted with native, LPS-stimulated PMN, and with PMN of sepsis patients revealed that, despite an increased adenosine A(2A) receptor (A(2A)R) expression, the receptor function declines due to a diminished ligand-binding affinity most likely caused by allosteric modulators within the inflammatory environment. A(2A)R function obviously is highly dependent upon the cellular environment and thus, further functional characterization of A(2A)R responses in sepsis may be a promising approach to develop new adenosine or A(2A)R agonists based therapeutic strategies.